The Bodhīsattva Path: An Anticipatory Path in Mahāyāna Buddhism - Bajracharya, Ranjana; Shakya, Sanjay (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Buddha and Bodhīsattva are the most praised words in Buddhism. The Mahāyāna texts like Guṇakāraṇdavyha, Sadharmapuṇḍarika, and Gaṇḍavyūha sūtra seem never exhausted praising philanthropic deeds of Bodhīsattvas. Buddha frequently describes his previous life to his pupils as Bodhīsattva. The Bodhīsattva vows to have the potential power to lead one to become Buddha. The word and its essence have precious value among Buddhists. The Bodhīsattva vows can lead to becoming Buddha as they have the potential to become one. In this respect, Bodhīsattvahood is an applied way of practicing dharma. The personification of the ideal concepts in Buddhism is commendable. Wisdom and compassion are two aesthetics in Buddhist philosophy incorporated and appreciated with the greatest Buddhist zeal. The wisdom of Mañjuśri and the compassion of Avalokiteśvara are beautiful emanations, praised practices of deification in Buddhism. Believing in the wisdom of Mañjuśri and the austerity of various emanations of Avalokiteśvara are hugely popular cult beyond the geographical constraints of Nepal. Yet, the development of Buddhist streams after the Mahāparinirvāṇa of the Buddha is not smooth. The library research method was implemented, with original sources taken into account for the authentication of the study. Various ideologies made an impact to develop 18 sects at the time of Emperor Asoka in India around the 3rd century BCE. The advent of Mahāyānic concepts like Buddhahood and Bodhīsattvahood led Buddhism to a whole new level in the world that is still witnessed with great Endeavour.